MENINGKATKAN HASIL BELAJAR SISWA KELAS VII.6 MELALUI MODEL DIRECT INSTRUCTION PADA MATA PELAJARAN SENI BUDAYA (MUSIK) DI SMP NEGERI 13 PADANG - Putri Dwi Hayati; Ardipal Ardipal; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2018)
Abstract This article aims to find out the results of increased student learning Class VII. 6 through direct instruction model on the subjects of art and culture (music) in SMP Negeri 13 Padang. The type of research was classroom action research. Classroom action research procedure consisted of four stages, they were planning, implementation, observation and reflection. Techniques of data collection were done by literature study, observation, test and documentation. The results showed that the application of direct learning model in the learning of art and culture (music) was very effective in improving student learning outcomes. From the learning process of student activity on cycle 1, it was found that the average of overall score of 1, 2 and 3 was 52%. While in cycle 2, the overall average score of meetings 1, 2 and 3 was 81%, the average student learning outcomes increased significantly from cycle 1 to cycle 2 with very good criteria. Judging from the data of the students' learning outcomes both written test and practice ability in the average pre cycle value 68 that increased in cycle 1 with the average value of 80 and cycle 2 with an average value of 85.3. Seen in the results of students' ability to practice improvement in each cycle that was in pre cycle had only has average score  67, cycle 1 with the average value of 80.3 and cycle 2 with an average value of 85. Keywords:                 Results of the Study, Direct Instruction Model, Cultural Art (Music),